MINIMIZE THE HYDROGENATION OF UNSATURATED FATTY ACID IN THE RUMEN WITH KAFFIR LIME (Citrus hystrix) - Nafly Comilo Tiven (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This research aimed to know the ability of citronella from C. hystrix to protect unsaturated fatty acid of Tropical cooking oil on the hydrogenation process by rumen microbes. The in vitro fermentation test used rumen fluid of local female sheeps as source of microbial, Tropical cooking oil as a source of unsaturated fatty acids and C. hystrix leaves as source of cironela. Tropical cooking oil was mixed with Preston skim milk (1:2). The mixture were added by C. hystrix leaves with the level of 0%, 1%, 2%, 3% and 4% (dry weight bases) from the weight of the mixture, then mixed evenly into protected Tropical cooking oil. The data was analyzed by Completely Random Design. The difference of means the treatments were tested by Duncan’s New Multiple Range Test. Result showed that oleic and linoleic resulting from fermenting Tropical cooking oil protected by citronela in C. hystrix was increase if it compare to unprotected. It can be concluded that Tropical cooking oil protected with citronelal C. hystrix was reduced hydrogenation of unsaturated fatty acid, mainly oleic and linoleic.